Financial evaluation of mining projects : a case study - Islam, Md. Mazhar ul; Gupta, Joyti; Jain, P. K.; Ramanathan, K.; DAAD (German) (Bangkok : Asian Institute of Technology, 1997)
Mining is a capital intensive industry. It has a long preproduction period and investment is also associted with risk. Financial evaluation plays an important role in the mineral industry . as on the basis of this study projects are undertaken for investment. It is more important for the developing countries point of view as mining activities can contribute substentially in the economy. In this research paper financial evaluation of the mining projects have been discussed and a real life case from a developing country has been analysed to broaden the understanding.
A research study submitted in partial fulfillment of the requirement for the Master of Business Administration
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 1997
Keywords: Mineral industries -- Finance